2020
DOI: 10.3390/s20102811
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Daily Terrestrial Latent Heat Flux with High Spatial Resolution from MODIS and Chinese GF-1 Data

Abstract: Reliable estimates of terrestrial latent heat flux (LE) at high spatial and temporal resolutions are of vital importance for energy balance and water resource management. However, currently available LE products derived from satellite data generally have high revisit frequency or fine spatial resolution. In this study, we explored the feasibility of the high spatiotemporal resolution LE fusion framework to take advantage of the Moderate Resolution Imaging Spectroradiometer (MODIS) and Chinese GaoFen-1 Wide Fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Therefore, the inclusion of Sentinel-2B in future studies will reduce the revisit cycles (Baillarin et al, 2012;Ma et al, 2021) and improve the temporal resolution of Sentinel-2 to reduce the effect of cloud rain on data fusion accuracy. However, the low spatial resolution of MODIS leads to a large number of mixed pixels within the data (Leckie, 1990), which makes it difficult to clearly express the spatial texture detail information among different features (Bei et al, 2020;X. Zhu et al, 2016); hence, this results in a delay in NDVI growing curves.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inclusion of Sentinel-2B in future studies will reduce the revisit cycles (Baillarin et al, 2012;Ma et al, 2021) and improve the temporal resolution of Sentinel-2 to reduce the effect of cloud rain on data fusion accuracy. However, the low spatial resolution of MODIS leads to a large number of mixed pixels within the data (Leckie, 1990), which makes it difficult to clearly express the spatial texture detail information among different features (Bei et al, 2020;X. Zhu et al, 2016); hence, this results in a delay in NDVI growing curves.…”
Section: Discussionmentioning
confidence: 99%
“…They are classified into two categories: enhanced spatial and temporal adaptive reflectance fusion model (ESTARFM) [218] and unmixing method. ESTARFM was tested by Bei et al [219], Tao et al [220] and Zeng et al [221], who all reported the enhancement of the fusion method for complex heterogeneous regions. Bei et al [219] tested the fusion of spatial and temporal adaptive reflectance fusion models (STARFM) with the ESTARFM with different spatiotemporal features.…”
Section: Laimentioning
confidence: 99%
“…where f wet is the relative surface wetness, f sm is soil moisture constraint, f T represents plant temperature constraint exp(−(T a − T opt /T opt ) 2 ), DT max describes the maximum diurnal air temperature range (40 • C), T opt is an optimum temperature (25 • C), R ns is the surface net radiation to the soil (R ns = R n (1 − f c )), G is soil heat flux (µR n (1 − f c ), µ = 0.18), R nv represents the surface net radiation to the vegetation (R nv = R n f c ), f v is the vegetation cover fraction, and NDV I min and NDV I max are the minimum and maximum NDV I, respectively. Compared with the MODIS LE product (MOD16), the MS-PT algorithm reduced the uncertainties by approximately 5 W/m 2 in the LE estimation and provided more reliable LE estimations at multiple biomes [14]. Therefore, the MS-PT was chosen to generate a spatiotemporal continuous LE product with 16 m daily resolution.…”
Section: Le Computationmentioning
confidence: 99%
“…However, due to the lack of detailed land surface information, its relatively coarse spatial resolution is not sufficient to characterize the variations of LE in heterogeneous areas [12]. With the emergence of new satellite sensors, such as the Chinese GaoFen-1 Wide Field View (GF-1 WFV) (16 m spatial resolution and frequent revisit cycle) and Sentinel-2 (a five-day cycle and 10 m spatial resolution), it has been possible to provide highly valuable data sources at fine spatial resolution [13,14]. Nevertheless, cloud contamination seriously interferes with image acquisition, contributing to a generally sparse temporal frequency.…”
Section: Introductionmentioning
confidence: 99%